Mechanical evaluation of the dilation force of dilation devices during interventional endoscopic ultrasound - Ogura, Takeshi; Ueno, Saori; Hakoda, Akitoshi; Okuda, Atsushi; Nishioka, Nobu; Sakamoto, Jun; Yamamura, Masahiro; Hattori, Nobuhiro; Bessho, Kimi; Nishikawa, Hiroki; Kanaoka, Rie; Kurose, Youhei (Endoscopy International Open, 2024)
Background and study aims To insert the metal stent delivery system (8.5F) during interventional endoscopic ultrasound (I-EUS), several dilation steps are needed, which may be related to increased bile leakage from a fistula. There have been no definitive studies of dilation force. The aim of the present study was to evaluate dilation force during I-EUS using several dilation devices.Methods In the present study, seven dilation devices were evaluated including bougie dilators such as a straight-shaped dilator (the ES dilator, Soehendra dilator, a standard ERCP catheter) a screw-shaped dilator (Tornus ES, Soehendra stent retriever), and a 4-mm balloon catheter (REN biliary balloon catheter, Hurricane RX). The diameter of each dilator and dilation force were measured.Results Of the bougie dilators, the dilation force of the ES dilator was the highest (0.908±0.035 kg). Of the balloon catheters, the dilation force of the Hurricane RX (3.261±0.024 kg) was slightly higher than that of the REN (3.159±0.072 kg). Of the bougie dilators, although the diameter of the ES dilator was not larger than that of the Tornus ES, the dilation force was stronger. Similarly, the diameter of the Soehendra stent retriever was greater than that of the ERCP catheter or Soehendra dilator and the dilation force was lower.Conclusions Compared with bougie dilators, balloon catheters have stronger dilation force according to our experimental study. The present results should be evaluated in clinical trials.
Keywords: Endoscopic ultrasonography; Intervention EUS; Biliary tract